Betty Crocker the big book of cookies. (Hoboken, N.J. : John Wiley, 2012)
"More than 180 cookies and bars recipes, from classics like cookie jar and bake sale favorites to holiday favorites and gift-giving cookies"--
Includes index.
COECSD
Keywords: Cookies; COOKING / Courses & Dishes / Cookies; Cookbooks